Integrasi Pasar Daging Sapi menggunakan Metode Vector Error Correction Model (Vecm) - Dwi Septiyarini; Sahbudin Sahbudin; Slamet Hidayah Sulaiman; Erlinda Yurisinthae (Universitas Muhammadiyah Purworejo, 2020)
Market integration is a measure that shows how far the price changes that occur in the reference market will cause price changes in the followers market. Domestic beef price fluctuations have the same tendency with world prices. Although fluctuations in domestic beef prices follow fluctuations in world beef prices, the integration of the global beef market with the domestic beef market is not certain. This study aims to analyze the level of price variation and integration of beef market in Pontianak. The coefficient of variation analysis is used to analyze the level of price variation and the cointegration approach with the Vector Autoregression (VAR) model to analyze market integration. The results showed that from the results of the VAR and VECM analysis in large markets and consumer markets in Pontianak City it can be said that in the long run between large markets and Consumer markets integration did not occur. In the short-term changes in consumer market cattle prices do not affect changes in large market cattle prices. Changes in large market cattle prices and consumer prices do not affect each other which indicates in the short term there is no integration between the two markets.